A gest\~ao urbana em arranjos transfronteiriços e os desafios de sua regulamentaç\~ao - Rosa Moura; Bolívar Pêgo Filho; Gustavo Ferreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– This text aims at a reflection on the configuration of cross-border arrangements, resulting from the advance of metropolization over the territory, its characteristics, and the difficulties they impose on the urban management process, due to constituting cities that break territorial borders of countries. Arrangements on the Brazilian border are enumerated, others from neighboring countries are discussed, and regulations, agreements and experiences that confirm or indicate positivities are evaluated, highlighting the Agreement on Bound Border Localities (ALVF), of Mercosur, celebrated in December 2019. The remaining and emerging challenges in these spaces are highlighted, demanding the adequacy of existing regulations and the agreement of new ones, based on appropriate instruments for the integration of continuous bi or tri-national urban spaces, and on policies that induce the formation of a power structure compatible with the nature of these spatialities, with authority over the organization of the territory and integrated planning.
10419/284865
Keywords: R11; R23; R38; R41; R58; 330; cross-border arrangements; metropolization; urban management; borders; Mercosur